Vancomycin‐Loaded Microneedle Arrays against Methicillin‐Resistant Staphylococcus Aureus Skin Infections. Issue 7 (5th May 2021) - Ziesmer, Jill; Tajpara, Poojabahen; Hempel, Nele‐Johanna; Ehrström, Marcus; Melican, Keira; Eidsmo, Liv; Sotiriou, Georgios A.
Abstract: Skin and soft tissue infections (SSTIs) caused by methicillin‐resistant Staphylococcus aureus (MRSA) are a major healthcare burden, often treated with intravenous injection of the glycopeptide antibiotic vancomycin (VAN). However, low local drug concentration in the skin limits its treatment efficiency, while systemic exposure promotes the development of resistant bacterial strains. Topical administration of VAN on skin is ineffective as its high molecular weight prohibits transdermal penetration. In order to implement a local VAN delivery, microneedle (MN) arrays with a water‐insoluble support layer for the controlled administration of VAN into the skin are developed. The utilization of such a support layer results in water‐insoluble needle shafts surrounded by drug‐loaded water‐soluble tips with high drug encapsulation. The developed MN arrays can penetrate the dermal barriers of both porcine and fresh human skin. Permeation studies on porcine skin reveal that the majority of the delivered VAN is retained within the skin. It is shown that the VAN‐MN array reduces MRSA growth both in vitro and ex vivo on skin. The developed VAN‐MN arrays may be extended to several drugs and may facilitate localized treatment of MRSA‐caused skin infections while minimizing adverse systemic effects. Abstract : The antibiotic vancomycin is delivered locally into the skin via microneedle arrays for potential treatment of methicillin‐resistant Staphylococcus aureus infections. The microneedle arrays consist of a water‐insoluble support layer surrounded by drug‐loaded, water‐soluble tips to ensure controlled administration of vancomycin. The performance of the arrays is explored in vitro and ex vivo for insertion capability, drug delivery, and antibacterial effect.